Reluctance To Speak In English Among Community College Students In Malaysia - Mahamud, Majdah (2018)
English is extensively used in industries. Therefore it is vital for our vocational and technology based students to be proficient in spoken English for a better local and international employment prospect. However many of the students were reluctant to speak in English in class. The mixed method study was concerned about the levels and correlations of communication apprehension perceived by the reluctant students in the Mother tongue and English, shyness and self-esteem. The respective levels were also measured according to courses and gender followed by a general description of a typical reluctant student.